Thermal burns of the spectacle associated with supplementary heating in native New Zealand geckos. Issue 2 (3rd March 2020) - Gartrell, BD; Ahn, JY; Khude, R; Dougherty, N; Johnson, K; McCutchan, J; Clarke, A; Hunter, S
ABSTRACT: Case history: Gradual onset of ocular opacity was observed in three gold-striped geckos ( Woodworthia chrysosiretica ), and five Pacific geckos ( Dactylocnemis pacificus ) held in two adjacent terrariums in a zoological institution located in the North Island of New Zealand. Ultraviolet light and heat had been provided for the previous 3–4 years by a fluorescent bulb, but in the last 4 weeks of winter a ceramic heat bulb had been added, situated 10 cm above the upper mesh of the cage Clinical findings: All eight geckos presented with mostly bilateral lesions of varying severity confined to the central or upper quadrant of the spectacles. These lesions ranged from variable areas of opacity within the stroma of the spectacle to similarly distributed ulcers of the surface epithelium of both spectacles. The spectacle lesions in the Pacific geckos responded well to treatment with topical combined antimicrobial therapy, within 18–29 days. The gold-striped geckos suffered complications including dysecdysis, severe spectacle ulceration and perforation, mycotic spectaculitis, and widespread mycotic dermatitis resulting in death or leading to euthanasia. Pathological findings: In the three gold-striped geckos, there were extensive areas of deep ulceration and replacement of the spectacle with a thick serocellular crust containing large numbers of fungal elements. The affected areas of the stroma were expanded by large deposits of proteinaceous and mucinous material, pyknotic cellular debris and moderate numbers of heterophils and macrophages as well as infiltrating fungal hyphae. Diagnosis: Mycotic spectaculitis with ulceration and perforation, and disseminated mycotic dermatitis likely secondary to thermal burns. Clinical relevance: This is the first report of thermal burns of the spectacle in any reptile. There was species variation in the burn severity with gold-striped geckos showing more severe lesions, possibly due to a mix of behavioural and anatomical factors. The thermal burns to the spectacles in three cases were complicated by delayed healing, perforation, dysecdysis and severe mycotic infection.